2015
DOI: 10.1016/j.bmcl.2014.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TRIF selectivity in the AGP class of lipid A mimetics: Role of secondary lipid chains

Abstract: TLR4 agonists that favor TRIF-dependent signaling and the induction of type 1 interferons may have potential as vaccine adjuvants with reduced toxicity. CRX-547 (4), a member of the aminoalkyl glucosaminide 4-phosphate (AGP) class of lipid A mimetics possessing three (R)-3-decanoyloxytetradecanoyl groups and D-relative configuration in the aglycon, selectively reduces MyD88-dependent signaling resulting in TRIF-selective signaling, whereas the corresponding secondary ether lipid 6a containing (R)-3-decyloxytet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Subsequent generations of what we now know to be TLR4 agonists (such as GLA/PHAD 2 , INI-2002 3 , or CRX-601 ( 4 )) are synthetic derivatives of MPL from which non-essential components have been removed. Minor modifications of the TLR4 agonists’ structures are able to significantly alter the resulting receptor signals ( 5 ). The latest generation of TLR4 agonists ( e.g ., 2B182c 4 or neoseptin ( 6 )) are small molecules that do not share structural similarities with the canonical receptor agonists.…”
Section: New Trends In Adjuvant Researchmentioning
confidence: 99%
“…Subsequent generations of what we now know to be TLR4 agonists (such as GLA/PHAD 2 , INI-2002 3 , or CRX-601 ( 4 )) are synthetic derivatives of MPL from which non-essential components have been removed. Minor modifications of the TLR4 agonists’ structures are able to significantly alter the resulting receptor signals ( 5 ). The latest generation of TLR4 agonists ( e.g ., 2B182c 4 or neoseptin ( 6 )) are small molecules that do not share structural similarities with the canonical receptor agonists.…”
Section: New Trends In Adjuvant Researchmentioning
confidence: 99%
“…Thus, GSK Biologicals developed aminoalkyl glucosaminide phosphates (AGPs) where the proximal GlcN ring of lipid A was omitted furnishing in this way a polar head group with rationalized structure [ 137 ]. Variable β-hydroxyacyl and alkyl chains were chemically attached to the polar head group and selected AGPs reached pre-clinical/clinical development which highlighted RC-529 as a potent vaccine adjuvant ( Figure 3 ) [ 138 ]. Lipid A mimetics containing pentaerythritol in place of proximal GlcN residue were developed by Biomira Inc. (Edmonton, AB, Canada) as potent cytokine secreting agonists.…”
Section: Choice Of Immunomodulationmentioning
confidence: 99%
“…23−26 These monosaccharide compounds consist of three fatty acyl chains that are N-and O-linked to an O-glucosaminyl ethylamine or serine backbone (e.g., 1a−c, Figure 1). We demonstrated that minor structural modifications to synthetic TLR4 agonists could alter signaling selectivity 27,28 (MyD88 vs TRIF bias in TLR4 agonists) and convert agonist to antagonist responses. 25 Engineered to specifically trigger an innate immune response with varying degrees of specificity, potency, and safety attributes, some of these agonists, in addition to showing promise as vaccine adjuvants, 29−33 were also capable of eliciting nonspecific protection against a wide range of infectious pathogens.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the course of our own structure–activity studies on a detoxified but complex form of lipid A known as 3- O -desacyl monophosphoryl lipid A (MPLA), a disaccharide TLR4 agonist, we developed a new class of synthetic monosaccharide TLR4-active glycolipids known as aminoalkyl glucosaminide 4-phosphates (AGPs), capable of eliciting robust innate and adaptive immune responses. These monosaccharide compounds consist of three fatty acyl chains that are N - and O -linked to an O -glucosaminyl ethylamine or serine backbone (e.g., 1a – c , Figure ). We demonstrated that minor structural modifications to synthetic TLR4 agonists could alter signaling selectivity , (MyD88 vs TRIF bias in TLR4 agonists) and convert agonist to antagonist responses . Engineered to specifically trigger an innate immune response with varying degrees of specificity, potency, and safety attributes, some of these agonists, in addition to showing promise as vaccine adjuvants, were also capable of eliciting nonspecific protection against a wide range of infectious pathogens. As evidence of the validity of this approach, the TLR4 agonist RC-529 was approved for human use in a recombinant HBV vaccine and another highly active TLR4 agonist, GSK1795091 (agonist 1c ), completed a phase I clinical trial for safety evaluation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation